KEY ISSUES OF INCREASING FINANCIAL LITERACY IN THE UZBEKISTAN EDUCATIONAL SYSTEM BASED ON ADVANCED FOREIGN EXPERIENCES - Abduvahitovna, Shamansurova Zilola (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
This article is devoted to the consideration of important issues of increasing the level of financial literacy in the educational system of Uzbekistan, especially in school education, and to the study of advanced foreign experiences. In the article, the financial literacy programs of different countries are analyzed and ways of their adaptation to the conditions of Uzbekistan are studied. Emphasizing that financial literacy has a positive effect on the economic stability and well-being of the population, the research notes the need for public and private sector cooperation, the organization of special courses and training in educational institutions, as well as the use of modern technologies and interactive methods. Proposals and recommendations developed on the basis of foreign experience are of great importance in the formation of practical programs aimed at increasing financial literacy in the school education system of Uzbekistan.